ANALYSIS OF CHARACTERS AND CHARACTERIZATION IN THE NOVEL HI BERLIN 1998 AND THEIR IMPLICATIONS FOR LITERATURE LEARNING IN HIGH SCHOOL - Gantini, Syalwa Romantika; Ansor Alsunah, Aditya; Nurwahidah, Lina Siti (Journal Of Educational Experts (JEE), 2026)
This study aims to analyze the characters and characterization in the novel Hi Berlin 1998 by Wahyuni Albiy. The research adopts a qualitative descriptive approach. The data consist of excerpts of dialogues, narrative scenes, and characters’ actions found in the novel. Data were collected through close reading and systematic note-taking techniques. The data analysis employed content analysis to interpret the characterization of each figure. The findings reveal that character and characterization constitute significant intrinsic elements of the novel. Characters are defined as individuals who participate in narrative events, while characterization refers to the author’s technique in depicting characters’ physical and psychological traits. The novel Hi Berlin 1998 presents eleven characters, which are classified into protagonists and antagonists. The protagonists include Sakeza Labiru, Jan Adam, Abarak, Hazel, Bryan, Julie, Erica, and Sakeza’s parents, whereas the antagonists are Araka Bentara and Vodka. Each character is portrayed with distinctive traits, physical descriptions, and unique characteristics that contribute to the development of the narrative.